The Phenomenon Crisis Management on Tourism Destination Development (Perspectives on Travel Management and Ergonomic Destination) - Mahadewi, Ni Made Eka; Irwanti, Ni Ketut Dewi (E-Journal of Tourism, 2022)
In every destination, crisis could be affecting the global tourism industry sector. Gurtner. Y (2007) assert that crisis management as a science, is still in its infancy largely due to the difficulties in standardizing, measuring, and comparing one crisis situation with another.  Usually crisis related to political issues, economic or social situation at the destination and distributed all over the world through numerous media channels.  This paper aimed at providing a combination concept of crisis management and ergonomic perspective. A model came to this study to answer the phenomenon of crisis management on tourist destination. By providing a literature-based overview on how a decline in visitor numbers due to crisis management and the destination do not implement the ergonomic components; an integrative model designed to know the answer why the numbers of visitor declined to tourist destination and why the income from tourism sectors decreased. The paper provides a literature-based theoretical and it implementation to Bali as tourist destination such as:   (1) the type of tourism crisis in Bali as a favorite tourist destination; (2) the tourism product and services of Bali tourism from ergonomic perspective; (3) the relationship of crisis and its supporting product and services for Bali tourism from ergonomic perspective; (4) the phenomenon crisis and its tourism development from ergonomic perspectives to quality and sustainability of Bali tourism; (5) an integrated model of crisis and ergonomic to quality tourism and Bali sustainability. Keywords: Tourism Crisis, Ergonomic Destination, Tourism Development, Travel Management